Breaking the Cycle: A Case of Child Maltreatment in a Problem Family - Jena, Beenit; kiran, Swosti; Salini, Reshma Asokakumar; Giri, Prajna (Indian Journal of Community Health, 2025)
Child maltreatment is a masked evil with multiple social phenomena influencing it. One in four adults reported having faced any form of maltreatment during their childhood. VACS (Violence Against Children and Youth Survey) reported that 23-54 % of children disclose their incidents of maltreatment, and of them, 25 % seek any help. Social factors such as caregivers’ educational status, Socioeconomic status, past experiences, low social support, and addictions pile up to form a problem family that lags behind the standard norms of the community. Children in such problem families may face challenges in cognitive development, academics, mental health, and forming healthy peer relationships due to instability and trauma. This case describes the negligence of the family, community, and administrative side in dealing with a case of child maltreatment.